(untitled) (International Journal of Ayurveda and Pharma Research, 2016)
Shakti drops an Ayurvedic polyherbal formulation is an effective medicine for immuno modulatory activity. The formulation was prepared in the laboratory with authenticated organic plant drugs. The standardization procedure was conducted on the basis of physicochemical parameters and antimicrobial studies as directed by Ayurvedic formulary of India. Antioxidant activity is further performed based on its prescribed dose in three In-vitro antioxidant models. Physical characters remained unaltered throughout study, In antimicrobial activity total aerobic count was found to be 18Ã—101 CFU/mL and total fungal count was found to be <10 CFU/mL. It is devoid of all tested microorganism i.e. Staphylococcus aureus, Salmonella typhi, Pseudomonas aeruginosa, Escherichia coli tested. In antioxidant activity the results of the study suggest that the Shiakti drops has potent antioxidant and free radical scavenging activity justifying its use in Rasayana.